The Role of Iron Oxide in The Characteristics of the Highly Weathered Soil - ACHMAD HIDAYAT; S. HARDJOWIGENO; M. SOEKARDI; SUPIYANDI SABIHAM (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2002)
Iron oxide is generaly found in the clay mineral composition of highly weathered soil (low activity clay soil) like Oxisols. There is limited information about the role of iron oxide in Oxisols, on the other hand the information is very important when we want to make use of the Oxisols. This study was done to investigate the role of iron oxide in the soilcharacteristic especially CEC, pHo, available water, plasticity index, soil color and maximum phosphate absorption. Soil samples were taken based on Soil Survey Staffs (1991), from different kinds of highly weathered soil i e: Typic Hapludox, Plinthic Hapludox and Anionic Acrudox, each sample was taken from two locations. At each location sample was taken from three different site : upper, middle and lower slope. Chemical analysis was done to determin the level of Fe.d, Fe.o, Fe.p, CEC (NH4OAc 1 M), pHo, available water, atterberg index and maximum phosphate absorption, and soil characteristics that useful for soil classification. Data were analyzed using matrix correlation test, simple and multiple regression. Principle Component Analysis was used to solve when multicolinearity problem happen. Results show that the Anionic Acrudox has the highest content of Fe.d and Fe.o, varied from 12.03 – 12.27% and1.01 – 1.12% . Followed by Typic Hapludox varied from 9.52 – 10.57% and 0.31 – 0.46% respectively for Fe.d and Fe.o. The level of Fe.d and Fe.o for Plinthic Hapludox varied from 6.31 – 9.40% and 0.09 – 0.17%. The higher the iron oxide content the lower the cation exchange capasity and the higher of the pHo. Multi regression analysis results between CEC and some soil characteristics shows that Fe.d and Fe.o can indicate thehighest variability namely 35.8%. While correlation between pHo and Fe.o shows the highest correlation and highly significant (r² = 0.65).Iron oxide has highly effect on available water and plasticity index, the higher the iron oxide content, the higher is the available water and the lower the plastisity index. The higher the iron oxide content the higher is intensity of red color of the soil. And the higher the iron oxide content, the higher is the maximum phosphate absorption; this condition is disadvantageus for plants, because the phosphate is not available for plants.